2022
DOI: 10.2147/pgpm.s372824
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-Related Gene – SLC31A1, FDX1 and ATP7B – Polymorphisms are Associated with Risk of Lung Cancer

Abstract: Background: Cuproptosis is a novel copper-dependent cell death, and the copper level was increased in lung cancer patients. However, few studies evaluated the association between single-nucleotide polymorphisms (SNPs) in cuproptosis-related genes and lung cancer risk. Methods: Six SNPs of the SLC31A1, FDX1 and ATP7B genes were genotyped in a case-control cohort including 650 lung cancer cases and 650 controls using the MassARRAY platform. Results:The minor alleles of SLC31A1-rs10981694 and FDX1-rs10488764 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…Patients with genomic instability of FDX1 had the disposition to poor survival in cancer patients. There has been a research on single-nucleotide polymorphisms (SNPs) in cuproptosis-related genes demonstrating that FDX1-rs10488764 was associated with an increased risk of lung cancer ( Yun et al, 2022 ). Further study is needed to explore the effect of FDX1 in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with genomic instability of FDX1 had the disposition to poor survival in cancer patients. There has been a research on single-nucleotide polymorphisms (SNPs) in cuproptosis-related genes demonstrating that FDX1-rs10488764 was associated with an increased risk of lung cancer ( Yun et al, 2022 ). Further study is needed to explore the effect of FDX1 in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed by Tsvetkov et al reported that excess copper contributes to the aggregation of lipoylated dihydrolipoamide S-acetyltransferase intracellularly, leading to a novel of mitochondrial cell death called "cuproptosis" (8,17). Increasing lines of evidence had constructed a cuproptosis-related signature for the prognosis and immune response of certain types of cancer (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer risk was shown to be elevated by the minor alleles of SLC31A1-rs10981694 and FDX1-rs10488764. In contrast, a lower incidence of the condition was associated with the minor alleles of rs9535826 and rs9535828 in ATP7B [37]. By using and analyzing a public database, some researchers investigated the relationship between cuproptosis-related genes and the prognosis of melanoma.…”
Section: Discussionmentioning
confidence: 99%